2022
DOI: 10.4081/dr.2022.9444
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of interleukin 1 beta in papule biopsies from patients with acne vulgaris

Abstract: Background: Acne vulgaris is the most common inflammatory disease of the skin. IL-1b has been found in acne lesions and is a promising target for therapy, but the evidence is limited. Therefore, this study was conducted to investigate the immunohistochemical expression of IL-1b in papule biopsies of inflammatory acne and its association with disease severity. Methods: This study involved 20 patients with acne vulgaris (13 females, median age: 22 years). Samples were taken using punch biopsy. Immunohistochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…Similar effects have also been reported in human peripheral neutrophils, monocytes and sebocytes [95][96][97]. Moreover, high levels of IL-1b are found in the skin lesions of acne patients [94,98]. Interestingly, it has also been recently proposed that only specific acneic strains of C. acnes are capable of triggering NLRP3-induced IL-1b production.…”
Section: Il-1 Subfamily and The Skin Microbiomesupporting
confidence: 74%
“…Similar effects have also been reported in human peripheral neutrophils, monocytes and sebocytes [95][96][97]. Moreover, high levels of IL-1b are found in the skin lesions of acne patients [94,98]. Interestingly, it has also been recently proposed that only specific acneic strains of C. acnes are capable of triggering NLRP3-induced IL-1b production.…”
Section: Il-1 Subfamily and The Skin Microbiomesupporting
confidence: 74%
“…Meng et al found that the expression of IL-1β in lesions of rosacea patients was significantly higher than age- and sex-matched healthy volunteers, especially PPR. In acne, all patients with inflammatory acne have dermal and epidermal IL-1β expression, and the expression level correlates with disease severity 16 . Ultraviolet B and P. acnes are triggers for IL-1β secretion, and the inflammation induced by P. acnes causes the massive secretion of IL-1β from monocytes 17 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Meng et al found that the expression of IL-1β in lesions of rosacea patients was signi cantly higher than age-and sex-matched healthy volunteers, especially PPR. In acne, all patients with in ammatory acne have dermal and epidermal IL-1β expression, and the expression level correlates with disease severity 13 . Ultraviolet B and P. acnes are triggers for IL-1β secretion, and the in ammation induced by P. acnes causes the massive secretion of IL-1β from monocytes [14][15][16] .…”
Section: Discussionmentioning
confidence: 99%